The brainwashing of my dad : how the rise of the right-wing media changed a father and divided our nation-- and how we can fight back - Senko, Jen (Sourcebooks, 2021)
"Author Jen Senko's father went from being a non-political, open-minded Democrat to a radical, angry, and intolerant right wing devotee, which eventually imploded the entire family dynamic. As politics began to take precedence over anything and everything, Jen was mystified at how these concepts began to insidiously seep into her father's mood and mindset. How had this happened? When and why had this started? Jen began the search for answers, and found them, in addition to an endless list of families just like her own. This isn't a story about just one man. It's the story of a media phenomenon that changed a father and eventually divided a nation."--